Japanese Public Diplomacy in Indonesia: The Role of Japanese Agencies in Academic Exchange Programs between Japan and Indonesia - A. Safril Mubah (Departemen Hubungan Internasional, Fakultas Ilmu Sosial dan Ilmu Politik, Unair, 2019)
Japan and Indonesia have developed mutual cooperation in academic exchange programs for the past three decades. Japan acknowledges that student interchange plays a significant role in promoting mutual understanding between Japan and foreign countries. Japanese government expects international students, either those who are still studying in Japan or those who have returned to their home countries, serve as a bridge between their countries and Japan. To achieve this goal, Japanese government employs some agencies to undertake academic exchange programs. In Indonesia, particularly, some Japanese agencies such as Japan Student Services Organization (JASSO), Japan Foundation, and Japan International Cooperation Center (JICE) have played important role in student exchanges. They have various programs to attract Indonesian students getting involved in academic exchanges. This paper describes these agencies’ role in academic exchange programs between Japan and Indonesia. Considering that the Japanese agencies work to promote Japan’s soft power through public diplomacy activities under transgovernmental networks model, I utilize concepts of public diplomacy and transgovernmental networks as a framework for analyzing the case. I argue that Japanese agencies have successfully served as Japanese public diplomacy agents by acting great role in advancing Japan’s soft power through academic exchange activities. However, some challenges appear in the way to achieve Japanese public diplomacy goal to create mutual understanding between Japanese and Indonesian people.